Effect of precursor and calcination time on the morphological structure and catalytic activity of Co\(_3\)O\(_4\) film in the oxygen evolution reaction - Nguyen Thi , Giang; Pham Hong, Hanh; Ngo Thi Anh , Tuyet; Vu Thi Kim , Oanh; Do, Linh; Nguyen Duc, Lam; Nguyen Thi, Mai; Bui, Hoa; Nguyen Thanh , Tung (Communications in Physics, 2024)
This research investigates the effect of cobalt precursor and calcination time on the morphology and catalytic activity of Co\(_3\)O\(_4\) films in the oxygen evolution reaction. Co\(_3\)O\(_4\) films with porous flower-like nanostructures were obtained using cobalt nitrate as a cobalt precursor, while cobalt chlorides were used to produce porous nanoneedle structures Co\(_3\)O\(_4\) film. Extended annealing time at temperature 350C caused structural fractures in the films. Among the samples, the synthesized Co\(_3\)O\(_4\) films were then evaluated as catalyst materials for the oxygen evolution reaction in alkaline 1M KOH electrolyte. Among synthesized films, the Co\(_3\)O\(_4\)-2-1h, synthesized using the cobalt chlorides as Co precursor and annealed at 350C for 1 hour, exhibited better oxygen evolution reaction catalytic activity. With its porous nanoneedle structure, the Co\(_3\)O\(_4\)-2-1h demonstrated superior performance comparable to the state-of-the-art 20% Ir/C catalyst. Moreover, the Co\(_3\)O\(_4\)-2-1h film demonstratesdemonstrated remarkable stability for the oxygen evolution reaction in a 1M KOH alkaline electrolyte.